Volume 14: Emerging Technologies; Engineering Management, Safety, Ethics, Society, and Education; Materials: Genetics to Struct 2014
DOI: 10.1115/imece2014-37553
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of the Tensile Strength of Fused Deposition Modeling Parts

Abstract: Acrylonitrile–butadiene–styrene (ABS) is a popular engineering thermoplastic and it is the most common material used in fused deposition modeling (FDM) technology. This technology is nowadays used for the production of prototypes and functional parts as well. It is therefore critical to know the mechanical properties of these parts, which, is as expected different from their nominal values. In this work the tensile strength of parts build with the FDM process is measured. ABS and ABS plus parts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 0 publications
2
22
0
3
Order By: Relevance
“…Out of these, the five process parameters namely, layer thickness (A), air gap (B), raster angle (C), build orientation (D), road width (E) have already been identified as the most significant FDM process parameters by several researchers [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] in their studies of FDM process optimization and therefore these main factors are considered in this paper to study their effects on the selected responses. The sixth parameter, the 'number of contours' is also considered in this study along with five main process parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of these, the five process parameters namely, layer thickness (A), air gap (B), raster angle (C), build orientation (D), road width (E) have already been identified as the most significant FDM process parameters by several researchers [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] in their studies of FDM process optimization and therefore these main factors are considered in this paper to study their effects on the selected responses. The sixth parameter, the 'number of contours' is also considered in this study along with five main process parameters.…”
Section: Methodsmentioning
confidence: 99%
“…A relatively large amount of research [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] have been performed to investigate the impact of process conditions on static mechanical properties (static loading) of the Acrylonitrile butadiene styrene (ABS) parts fabricated by FDM process using empirical models and applied design of experiments through statistical techniques such as regression analysis and analysis of variance (ANOVA). Unfortunately, a systematic experimental investigation of the effect of input parameters on the rheological and dynamic mechanical properties of part manufactured by FDM does not exist in the literature.…”
Section: Development Of the Regression Models Aim To Better Understanmentioning
confidence: 99%
“…The modulus and strength of 3D printed CA parts compare favorably to those of thermoplastic AM parts made by extrusion and laser sintering, including acrylonitrile butadiene styrene (ABS) (E = 1.6 GPa, σ = 22-34 MPa), [20,21] polylactic acid (PLA) (E = 1.5 GPa, σ = 39 MPa), [22] and Nylon (E = 0.2-2.6 GPa, σ = 50-58 MPa). [23][24][25] Additionally, the well-known anisotropy of AM thermoplastics made by fused deposition modeling (FDM) is a major limitation that is overcome here using CA.…”
Section: Doi: 101002/admt201600084mentioning
confidence: 99%
“…Unlike isotropic materials that have uniform properties in all directions, anisotropic material's properties such as Young's Modulus, change with direction along the object. Common examples are wood and composites(Lovelady, 2013) Savvakis, et al (2014),. specifically studied the mechanical properties of parts manufactured using fused deposition modeling or fused filament manufacturing methods, noting an anisotropic behavior in their tested specimens.…”
mentioning
confidence: 99%
“…Final part strength in parts fabricated using FDM technology is highly dependent upon the quality of inter-filament bonding within each layer.Material temperatures are set and adjusted by operators in the build parameters and controlled by feedback sensors located in the material liquefier. Previous research has indicated that material temperature profiles may vary significantly throughout the process traveling from the liquefier, out of the extrusion nozzle, and as it is deposited on the build platform.Other research studies have investigated the tensile strength of FDM/FFM fabricated parts Savvakis, et al (2014),. tested specimens built as solids using Stratasys build standards that produce parts with fill rates of about 97%.…”
mentioning
confidence: 99%